Antibiotic Resistance prevention in Developing Countries Like Bangladesh : A Narrative Review (Bangladesh Renal Journal, 2026)
Antibiotic resistance (AR) has emerged as one of the greatest public health challenges globally, disproportionately affecting developing countries such as Bangladesh. The burden is intensified by widespread misuse of antimicrobials, inadequate diagnostic capacity, weak regulatory systems, over-the-counter access, poor infection prevention and control (IPC), suboptimal sanitation, and limited antimicrobial stewardship (AMS) programs. Bangladesh, like many low-resource South Asian nations, faces rapidly rising resistance among gram-negative organisms, methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant enterococci (VRE), extended-spectrum â-lactamase (ESBL)-producers, and carbapenem-resistant Enterobacterales (CRE). This narrative review summarizes the magnitude, drivers, consequences, and evidence-based strategies for antibiotic resistance prevention in Bangladesh and similar settings. Emphasis is placed on AMS in hospitals and the community, surveillance strengthening, One Health approaches, vaccination, water–sanitation–hygiene (WASH) improvements, regulatory reforms, and public awareness. The review also highlights successful global and regional interventions that may be adapted for Bangladesh.Bang. Renal J. 2026; 8(1): 30-34